The influence of habitat structure on energy allocation tactics in an estuarine batch spawner. (5th April 2016) - Brigolin, D.; Cavraro, F.; Zanatta, V.; Pastres, R.; Malavasi, S.
Abstract: Trade-off between fecundity and survival was tested in a batch spawner, the Mediterranean killifish Aphanius fasciatus, using an integrated modelling-data approach based on previously collected empirical data. Two sites of the lagoon of Venice (Northern Adriatic sea, Italy) were selected in order to compare the energy allocation between growth and reproduction in two contrasting habitats. These were characterised by high and comparable level of richness in basal resources, but showed two different mortality schedules: an open natural salt marsh, exposed to high level of predation, and a confined artificial site protected from piscivorous predation. By means of a bioenergetic Scope for Growth model, developed and calibrated for the specific goals of this work, we compared the average individual life history between the two habitats. The average individual life history is characterised by a higher number of spawning events and lower per-spawning investment in the confined site exposed to lower predation risk, compared to the site connected with the open lagoon. Thus, model predictions suggest that habitat structure with different extrinsic mortality schedules may shape the life history strategy in modulating the pattern of energy allocation. Model application highlights the central role of energy partitioning through batch spawning, in determining the life history strategy. The particular ovary structure of a batch spawner seems therefore to allow the fish to modulate timing and investment of spawning events, shaping the optimal life history in relation to the environmental conditions.